PENGELOLAAN WEBSITE SEBAGAI MEDIA INFORMASI PUBLIK PADA BAGIAN HUMAS DAN INFORMASI PEMERINTAH KOTA PEKANBARU - Wardah, Mardhatillah; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Government of Pekanbaru city through the Government Secretariat division of Public Relations and Information manage the government's official website as a public information media. Pekanbaru City Government utilize IT facilities for the benefit of the public administration. In managing the website, PR and information seeks to make changes and improvements through public relations management. This study aims to determine the management process of public relations in managing the website as a public information media covering identifikasian problem, Planning, Action and Communication and Evaluation.This study used qualitative research methods. The informant of this study is the head of the sub-sections and 3 staff manager of information and complaints from the public, while the object of this study is the management of the website as a public information media. The data collection technique used was observation, interviews and documentation. In reaching the validity of the data in this study, the authors used the extension of participation and triangulation. The results showed that the management of the website as a public information media in the public relations and information using public relations management process. First identifying the problem is the public relations and information has made observations related to management of the website as a public information media. PR seeing community needs to be able to communicate with the mayor and officials. Furthermore, PR and information to make planning in the management of the website by creating IT-based public complaints program and coordinate with officials managing information and documentation, as well as forming a team to answer all the aspirations and the incoming news in the websites. Next in action and communication, PR run the activities of cyber PR in managing websites, public relations staff to answer incoming aspirations, manage the news, as well as the input of data in the Website content www.Pekanbaru.go.id. Recently, PR evaluate at the end of the year, publicist made recap complaints and conduct meetings related devices, human resources and the performance of the PR staff at the sub-section manager of information and complaints from the public in the management of the website as a public information media. Keywords: Pekanbaru City Government, Public Relations Management, Cyber PR, website